Advances in stem cell therapy for amyotrophic lateral sclerosis. (3rd August 2018) - Mazzini, Letizia; Ferrari, Daniela; Andjus, Pavle R; Buzanska, Leonora; Cantello, Roberto; De Marchi, Fabiola; Gelati, Maurizio; Giniatullin, Rashid; Glover, Joel C.; Grilli, Mariagrazia; Kozlova, Elena N.; Maioli, Margherita; et al.
ABSTRACT: Introduction : Amyotrophic Lateral Sclerosis (ALS) is a progressive, incurable neurodegenerative disease that targets motoneurons. Cell-based therapies have generated widespread interest as a potential therapeutic approach but no conclusive results have yet been reported either from pre-clinical or clinical studies. Areas covered : This is an integrated review of pre-clinical and clinical studies focused on the development of cell-based therapies for ALS. We analyze the biology of stem cell treatments and results obtained from pre-clinical models of ALS and examine the methods and the results obtained to date from clinical trials. We discuss scientific, clinical, and ethical issues and propose some directions for future studies. Expert opinion : While data from individual studies are encouraging, stem-cell-based therapies do not yet represent a satisfactory, reliable clinical option. The field will critically benefit from the introduction of well-designed, randomized and reproducible, powered clinical trials. Comparative studies addressing key issues such as the nature, properties, and number of donor cells, the delivery mode and the selection of proper patient populations that may benefit the most from cell-based therapies are now of the essence. Multidisciplinary networks of experts should be established to empower effective translation of research into the clinic.